Many-particle correlations and boundary conditions in the quantum kinetic theory - Morozov, V.G.; Röpke, G. (Condensed Matter Physics, 1998)
The problem of many-particle correlations in different approaches to the
quantum kinetic theory is treated on the basis of Zubarev's method of
the nonequilibrium statistical operator. It is shown that long-lived correlations can be incorporated through boundary conditions for reduced manyparticle density matrices and the nonequilibrium real-time Green functions.
Within the method of Green functions the boundary conditions are conveniently formulated in terms of the “mixed” Green functions deﬁned on a directed contour with the real-time evolution governed by the Hamiltonian of
the system and the “imaginary-time” evolution governed by the entropy operator. The perturbation expansion of the mixed Green function is obtained
in terms of the interaction part of the Hamiltonian and the correlation part
of the entropy operator. Проблема багаточастинкових кореляцій у різних підходах квантової кінетичної теорії розглядається на основі методу нерівноважного статистичного оператора Д.М.Зубарєва. Показано, що довгоживучі кореляції можуть бути враховані через граничні умови для зведених багаточастинкових матриць густини та нерівноважні функції
Ґріна дійсного часу. В рамках методу функцій Ґріна граничні умови
зручно формулюються в термінах “змішаних” функцій Ґріна, які визначаються прямим контуром з дійсним часом еволюції, що керується гамільтоніаном системи, та “уявним” часом еволюції, що керується оператором ентропії. Розклад за збуреннями змішаних функцій
Ґріна отримано в термінах частини гамільтоніана, що відповідає за
взаємодію, та кореляційної частини оператора ентропії.